Strategy to Increase Investment Portfolio at Retired Priority Banking Customers of PT Bank Rakyat Indonesia Yogyakarta Adisucipto Branch Office - Vira Putri Indra Kusuma; Bagus Panuntun (Publikasi Inspirasi Indonesia, 2024)
This study aims to determine the strategy of increasing investment portfolio for retired priority banking customers at PT Bank Rakyat Indonesia Yogyakarta Adisucipto Branch Office. Bank Rakyat Indonesia Yogyakarta Branch Office Adisucipto is a company under the auspices of the Head Office of Bank Rakyat Indonesia located in Yogyakarta. The research method used in this study is by using observation, interviews, and documentation. This research data is sourced from primary data obtained through data collection techniques based on the process of observation, documentation, and interviews conducted directly to companies and retired priority banking customers who meet the criteria, as well as secondary data obtained from quoting books, internet, and so on containing information about priority banking Bank BRI. Therefore, researchers are able to draw conclusions descriptively. The interview was conducted with 5 respondents who are employees and customers of retired priority banking Bank BRI Yogyakarta Branch Office Adisucipto. The results of this study show what investment products are suitable to be offered to retired priority banking customers and how the profitability of investment products owned by retired priority banking customers for BRI Prioritas. The author recommends increasing the offering of certain investment products and the Bank strengthening the implementation of ESG especially Environmental principles.